(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
Uzbekistan is achieving many successes as a result of rational economic reforms in its new stage of development. In recent years, the economic potential of our national economy has increased; it has gradually gotten rid of the bureaucratic system and has entered the path of development based on the free economic requirements of the market. Economic cooperation is also developing in the international arena, and the economic relations of our country with foreign countries are expanding.